Analisis Faktor-Faktor Yang Mempengaruhi Pilihan Perusaahan Terhadap Konservatisme Akuntansi Pada Perusahaan Manufaktur Yang Terdaftar Di BEI - Evi Vidiana; Diana Dwi Astuti; Wiwik Fitria Ningsih (JAKUMA : JURNAL AKUNTANSI DAN MANAJEMEN KEUANGAN, 2020)
The principle of accounting conservatism is still considered a controversial principle on the one hand accounting conservatism is considered as an obstacle that will affect the accounting conservatism as the dependent variable, then managerial ownership quality of financial statements, on the other hand accounting conservatism is useful to avoid managers' opportunistic behavior with regard to contracts used by financial statements as contract media. used in this research is, public ownership, debt governance, grow opportunities and capital intensity are used as factors that can influence conservatism as well as being an independent variable. The sample of this research is manufacturing companies listed on the Indonesian stock exchange (IDX). Samples are selected using the purposive sampling method. The number of companies taken as samples are 5 companies from 14 companies in 2014-2018. The results of research from research this is that from the five variables namely managerial ownership, public ownership, debt covenant, growth opportunities and capital intensity, there are three variables that have a significant influence on accounting conservatism.